The digital factory the human labor of automation - Altenried, Moritz (University of Chicago Press, 2022)
"In recent years, tech companies such as Google and Facebook have rocked the world as they have seemingly revolutionized the culture of work. We've all heard stories of lounges outfitted with ping pong tables, kitchens with kombucha on tap, and other amenities that supposedly foster creative thinking. Nothing could seem further from earlier workplaces associated with a different revolution in capitalism: factories, in which employees are required to perform highly circumscribed tasks as quickly as possible to meet quotas--for next to no pay. However, as Moritz Altenried shows in The Digital Factory, these types of workplaces are not so far from the Googleplex as we might think. While recent accounts of the transformation of labor after the demise of the factory highlight the creative, communicative, immaterial, or artistic features of contemporary labor, Altenried uncovers the factory-like conditions in which many new digital workers perform their jobs. These workers, such as video game testers, social media content moderators, and Amazon fulfillment center workers, perform highly repetitive, unskilled tasks for low and often contingent wages. Based on more than five years of research in different sites using ethnography and interviews combined with an analysis of infrastructural technologies, Altenried's book gives us a first-hand account of many new forms of digital labor that drive contemporary capitalism. He shows that though today's factories might look and feel different than they did 150 years ago, they still follow the same logics and produce the same unequal outcomes"--